2020
DOI: 10.25299/jshmic.2020.vol7(2).5339
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Direct Language Learning Strategies and English Learning Proficiency at Senior High School Students

Abstract: Learning strategies are applied by students to improve their studies. Suitable language learning strategies result in proficiency which is improved and greater self-confidence. Most researches observe the language learning strategies without dividing which affect more between direct and indirect strategy toward learning proficiency. Therefore, this research was conducted to find out whether the direct language learning strategies had a positive relationship and significant effect toward English learning profic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…This could also suggest that students´ language proficiency may be also affected by other external factors apart from the online course content and LLS activities. Additionally, even though this study results are as similar as other studies which also used the OPT to assess language proficiency in terms of grammar, vocabulary and reading skills (Enayat, & Amirian, 2016;Mohammadi & Izadpanah 2019;Tavakoli et al, 2014), this test seems to be limited to assess other aspects of language proficiency such as speaking, writing and listening which can also provide a broader picture of students´ English proficiency (Arisman, 2020;Tavakoli et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This could also suggest that students´ language proficiency may be also affected by other external factors apart from the online course content and LLS activities. Additionally, even though this study results are as similar as other studies which also used the OPT to assess language proficiency in terms of grammar, vocabulary and reading skills (Enayat, & Amirian, 2016;Mohammadi & Izadpanah 2019;Tavakoli et al, 2014), this test seems to be limited to assess other aspects of language proficiency such as speaking, writing and listening which can also provide a broader picture of students´ English proficiency (Arisman, 2020;Tavakoli et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…The definition of LLS involves the conscious reasoning and actions to make possible the process of language learning (Shakarami, Hajhashemi & Caltabiano, 2017). LLS can also be described as processes and behaviors in order to achieve learning goals regardless of the content and context (Arisman, 2020). According to Oxford (1990) LLS are divided into direct strategies such as memory, cognitive and compensation; and indirect strategies which are metacognitive, social and affective.…”
Section: Language Learning Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The study employed the ex-post facto research design, especially correlation method to describe an occurred event accurately and relate among variables (Coral et al, 2018;Elyas, & Alghofaili, 2019;Arisman, 2020). The study accurately identified the brain dominance, learning style profiles and reading proficiency of English as a Foreign Language (EFL) students.…”
Section: Methodsmentioning
confidence: 99%